The Attitudes of EFL Learners on Using Mall in English Online Classroom - Cahyaningrum, Aulya; Indriani, Lilia (IJET (Indonesian Journal of English Teaching), 2022)
In the era of easiness because of the development of modern things correlated with language, almost all human life aspects should include those. Nowadays almost nothing who do not know how to access technology, including EFL learners. Besides this research aims to identify EFL learners’ attitudes toward using MALL for online English classes. Technology role and learners’ ability to utilize it are considered significant after the global pandemic was announced, which drove all education activities to be fully online. One of the subjects that can greatly benefit from technology is English, since almost everyone worldwide enhances its technology. To achieve the goals of this study, a descriptive qualitative method was used, with a questionnaire adopted from Jebur and interviews conducted with 52 EFL learners at Tidar University who had completed a two-year English online course as a result of the pandemic outbreak. The result shows that the positive attitudes of most EFL learners are visible toward the use of mobile phones in English online classes. It can be a benefit in some cases, yet need another media where it could be depending on each learner’s preference. In conclusion, teachers should be aware of each learner to provide authentic media for particular class purposes. However, this research would benefit for the newest data to the readers or researchers in this certain field to make further improvements.